Hubungan Konsep Diri dengan Perilaku Merokok Pada Remaja Kelas VIII di SMP Negeri 3 Pekanbaru - Sintia Miranda; Usraleli Usraleli; Masnun Masnun; Wiwiek Delvira; Rusherina Rusherina (Universitas Batanghari Jambi, 2020)
Smoking is an easily imitated adult behaviour and is the most noticeable behavior in demonstrating the attitude of maturity. Smoking can be a way for the youth to have them appear free and mature as they adapt to their peers. The decision to smoke may be a reflection of the problem of self-concept and influenced by culture (Potter and Perry, 2010). The concept of self develops gradually as babies begin to recognize and distinguish themselves from others. The formation of this self concept is strongly influenced by the care of parents and their environment (Tarwoto and Wartonah, 2011). The purpose of this research is to know the self-concept relationship with smoking behavior in class VIII teenagers in SMP Negeri 3 Pekanbaru. This research uses cross sectional methods. The population in this study amounted to 83 people. Sampling uses a total of 83 people. Data collection is performed using questionnaires. Data is analyzed univariate and bivariate. The results showed the teenage grade VIII teenagers in SMP Negeri 3 Pekanbaru had a low self concept as much as (53%) and adolescents who behave as much as (57.8%). And the results of statistical test Show (p value = 0.001) means there is a significant relationship Asntara self-concept with the behavior of smoking in class VIII teenagers in SMP Negeri 3 Pekanbaru. The results of this research can be used as input for the school to be more firmly sanctioned and more stringent in the overseas students in the school environment to prevent the occurrence of smoking behavior in students. Parents are expected to supervise the child who performs the smoking behavior.